Pengaruh Mekanisme Corporate Governance dan Investment Opportunity Set (IOS) terhadap Nilai Perusahaan dengan Kualitas Laba Sebagai Variabel Mediasi - Nilam Eka Putri; Erly Mulyani (Jurnal Eksplorasi Akuntansi, 2023)
The purpose of this study was to determine the direct effect of corporate governance mechanism (managerial owners and institutional owners) and investment opportunity set (IOS) on firm value and the indirect effect through earnings quality as a mediating variable. The sample used is 10 state-owned companies registered on the Indonesian stock exchange during the period 2016-2020. This study used SEM-PLS analysis technique to analyze the data. The results of this study show that managerial ownership, institutional ownership and investment opportunity set (IOS) have no significant effect on earnings quality directly. Meanwhile, there are significant effect on managerial ownership, institutional ownership, investment opportunity set (IOS) and earnings quality to firm value. The result also shows that earnings quality as mediating variable is not able to mediate the relationship between managerial ownership, institutional ownership, investment opportunity set (IOS) and firm value.